A Study on Consumers Perception on Halal Certification of Dietary Supplement Products. - Abdul Aziz, Norazlina binti; Saripan, Hartini; Mohamed, Farizah; Bakar, Mardiah Hayati Abu (International Journal of Psychosocial Rehabilitation, 2020)
The global health industry market perceives an enormous potential of profit within the dietary supplements business. Contributed by the changes in consumer perception in accepting that supplements aids in prevention of diseases, the number of supplements available to consumers has seen tremendous growth. As the supplements industry expanded with new innovations and advanced of technology, the consumers lose transparency in knowing the process, composition and ingredients of the dietary supplement products. They are expose to many risks of the dietary supplement products that includes the safety, efficiency and quality aspects. Certifying the supplements as halal may safeguard the safety, efficiency and quality of the products as halal is attached to the concept of ‘thoyibban’ that upon compliance will accord assurance on the safety, efficiency and quality of the product. In suggesting for the reformation of current consumer protection on this area, the study intends to analyse the effects of halal certification on dietary supplement products to the consumers. The ultimate aim of the study is to answer questions whether there is a significant effect attaching halal certification on the dietary supplement products to boost the confidence of the consumer on the safety, efficacy and quality aspect of the products. This will assist in the direction of reformation over the current consumer protection framework. The study adopts a mix method of qualitative and quantitative methods. The qualitative method embarks on analyzing the fundamental principle of ‘halalan thoyibban” and its relation to the assurance of safety, efficiency and quality of dietarysupplements products. The analysis of data acquired through qualitative method involve content analysis approach on traditional and contemporary sources of Islamic laws. The data acquired through content analysis is supported by semi-structured interviews with respondents that has been selected through purposive approach. The second part of the study uses quantitative method by distribution of questionnaires to selected consumers of dietary supplement products. The findings to the study disclose the effects of halal certification on dietary supplements product that may assist the policy maker and industry to make appropriate reformation to the consumer protection framework within this industry.